Child with basket standing on Steadman Ave., Nome, March 30, 1907 - Nowell, Frank H., 1864-1950 (1907)
Caption on image: Steadman Ave., Nome, Alaska, Mar 30th 1907. F.H. Nowell, 5346 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number